PENGARUH VIDEO ANIMASI TERHADAP PENGETAHUAN DAN SIKAP ANAK SEKOLAH DASAR TENTANG OBESITAS - Agnes Sihsinarmiyati; Demsa Simbolon; Widia Lestari (Poltekkes Kemenkes Bengkulu, 2021)
Obesity increases very sharply throughout the world which is quite alarming. One age group that is at risk of obesity is school age children. Animated video can provide real stimulation containing images, motion and sound elements. This study aims to determine the Effect of Animation Videos on Knowledge and Attitudes of Elementary School Children. This type of research is used Quasi Experimental with a pretest-posttest design with control group design. This research was conducted at SDN 01 and SDN 04 Kota Bengkulu on March 8 to April 8, 2019. Samples with 28 in each group. Analyze data using Mc. Nemar. The results of this study indicate that changes in knowledge before and after intervention in the intervention group (p = 0.0001), while in the control group (p = 0.001). Changes in attitudes of elementary school children before and after treatment in the intervention group (p = 0.063) and in the control group (p = 0.125). There is a change in knowledge but there is no change in attitude on the group and the intervention of the influence of the animation video on the knowledge of elementary school children about obesity in the city of Bengkulu.